2011
DOI: 10.1017/s0043933911000055
|View full text |Cite
|
Sign up to set email alerts
|

The structural model of relations between country of origin and the perceived brand name value

Abstract: The article investigates the importance of values of the perceived brand name from the external point of view perceived by the sample of consumers. Based on the stratified survey and the quantitative research the relationship between country of origin (COO), marketing mix elements and the perceived brand name value was noted. The emphasis is placed on establishing an impact of COO on the perceived brand name value and its impact on the latter compared to the selected marketing mix elements. The article present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The percentage of persons interviewed who buy both meat of domestic and foreign origin is 18 %.We can thus confirm there is a significant tendency towards purchasing fresh poultry meat of domestic origin. Similar results about attitude toward the origin of meat were obtained in a study of Strašek (2011) andVukasovič (2012). Also the results of these authors confirm the importance of meat origin in consumer decision-making process.…”
Section: Options Challenges and Potentials Of Poultry Meat: An Empirsupporting
confidence: 83%
“…The percentage of persons interviewed who buy both meat of domestic and foreign origin is 18 %.We can thus confirm there is a significant tendency towards purchasing fresh poultry meat of domestic origin. Similar results about attitude toward the origin of meat were obtained in a study of Strašek (2011) andVukasovič (2012). Also the results of these authors confirm the importance of meat origin in consumer decision-making process.…”
Section: Options Challenges and Potentials Of Poultry Meat: An Empirsupporting
confidence: 83%
“…A study conducted in Slovenia revealed that meat origin information significantly affected the perceived value of the selected properties of Slovenian chicken meat (Strašek, 2010). The author also found that the country of origin (COO) had a statistically significant influence on the perceived brand name value of the product compared with the selected marketing mix elements of the product (Strašek, 2011).…”
Section: Consumers' Behaviormentioning
confidence: 99%
“…European countries (Strašek, 2010(Strašek, , 2011Vukasovič, 2009Vukasovič, , 2010Vukasovič, , 2011. However, COO can be taken as search attribute for poultry meat.…”
Section: Fruit and Vegetable Consumers' Behavior 215mentioning
confidence: 99%
“…Food quality parameters explain 14 percent variation and are loaded on meat from healthy animal, age of animal, and hygienic conditions while processing. Using country of origin (COO) as an indicator of quality and safety, several researchers have also concluded that COO plays a very important role in influencing the buying behavior of consumers for poultry meat in European countries (Vukasovič, 2010(Vukasovič, , 2011Strašek, 2011).…”
Section: Consumers' Response On Product Attributesmentioning
confidence: 99%